Perpindahan Tenaga Kerja Non Pertanian Ke Tenaga Kerja Pertanian Pada Masa Pandemi Covid-19 Di Desa Woloan II Kota Tomohon - Kaemba, Adrian; Talumingan, Celcius; Waney, Nordy Fritsgerald Lucky (AGRI-SOSIOEKONOMI, 2023)
The purpose of the study was to determine the transfer of non-agricultural labor to agricultural labor during the Covid-19 pandemic in Woloan II Village, Tomohon City. The research lasted for three months from August to October 2022. The research was conducted in Woloan II Village, West Tomohon Sub-district. The data collected included primary data obtained through interviews using questionnaires, to labor respondents who moved from the non-agricultural sector to the agricultural sector during the Covid-19 pandemic. Secondary data were collected through research reports through the internet, journals, and other information related to the research. The sample in this study is workers in Woloan II Village, Tomohon City who have moved from the non-agricultural sector to the agricultural sector during the Covid-19 pandemic. Data were collected using purposive sampling with a sample of 15 respondents. The data is presented in a table and then described descriptively. The results of the research on the transfer of non-agricultural labor to agricultural labor in Woloan II Village, West Tomohon Subdistrict during the Covid-19 pandemic showed that the transfer to the agricultural sector with the rice commodity received a percentage of 46.67 percent and the second largest was the cabbage commodity of 40.00 percent and for the corn commodity had a percentage of 13.33 percent.